2005
DOI: 10.1093/rheumatology/kei101
|View full text |Cite
|
Sign up to set email alerts
|

Thymus alterations and systemic sclerosis

Abstract: The present study suggests a possible role of thymic disorders, mainly thymus hyperplasia, in a significant number of SSc patients. Due to the limitations of radiological evaluation, the actual relevance of such an association might be underestimated. The relationship of thymus alterations with shorter disease duration, as well as with serum anti-Scl70, suggests that thymic dysfunction could play a pathogenetic role mostly in the early phases of the disease, and possibly in specific SSc patient subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…In addition, focal massive clustering of follicles (>3 follicles per LPF) was considered as an additional criterion of high‐grade TFH. This grading system correlates with findings reported in the literature: few follicles are seen in up to one‐third of the lobules (as in grade 1 TFH) in healthy infants or adults, while TFH of grades 2–3 (in two‐thirds or more lobules) are typical for EOMG but rarely occur in other autoimmune diseases . By contrast, follicular clustering (grade 4 TFH) appears to be almost pathognomonic for EOMG …”
Section: The Thymus In Eomgsupporting
confidence: 87%
“…In addition, focal massive clustering of follicles (>3 follicles per LPF) was considered as an additional criterion of high‐grade TFH. This grading system correlates with findings reported in the literature: few follicles are seen in up to one‐third of the lobules (as in grade 1 TFH) in healthy infants or adults, while TFH of grades 2–3 (in two‐thirds or more lobules) are typical for EOMG but rarely occur in other autoimmune diseases . By contrast, follicular clustering (grade 4 TFH) appears to be almost pathognomonic for EOMG …”
Section: The Thymus In Eomgsupporting
confidence: 87%
“…In our present study, we observed a dramatic involution of the thymus in 15 week old Hexb −/− FcRγ +/+ mouse. The thymus plays a crucial role in immune system homeostasis, and thymic abnormalities have been previously reported in many autoimmune diseases, such as myasthenia gravis [31], systemic sclerosis [32], in a mouse model of systemic lupus erythematosus [24], and multiple sclerosis [33]. Since autoimmunity is found also in SD, the contribution of thymus abnormalities to the pathogenesis of this disease seems plausible.…”
Section: Discussionmentioning
confidence: 89%
“…An adverse intrauterine environment seems to cause thymus dysfunction and subsequent long-term immunologic deregulation, 26 and it was significantly more likely to find incomplete thymus involution in SSc and patients with rheumatoid arthritis than in a nonautoimmune control group. 27 Several studies have demonstrated that cesarean delivery, which often is associated with stressful intrauterine conditions, is linked to shortterm consequences for the newborn infant and increased risk of asthma, allergies, and type 1 diabetes mellitus in adulthood.…”
Section: Commentmentioning
confidence: 99%